2020
DOI: 10.2196/20165
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Self-Monitoring Rheumatoid Arthritis With a Smartphone App: Results of Two Mixed-Methods Pilot Studies

Abstract: Background Several mobile apps that monitor symptoms of rheumatoid arthritis (RA) exist, but a recent systematic review indicated that high-quality apps are lacking. When patients self-monitor their own disease with patient-reported outcomes (PROs) and self-initiate care at the right moment, it may be possible to reduce the frequency of their clinic visits, which would reduce health care burden and costs. We developed an app, that is, the MijnReuma Reade app, for this purpose and performed 2 pilot … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 32 publications
(36 reference statements)
3
44
1
1
Order By: Relevance
“…Our data showed that App use for self-reporting of symptoms is feasible longitudinally, and retention rate after 3 months was still high in MiDEAR. Thus, as reported from other ePROM studies, the App use might contribute to optimized patient–doctor interactions and care [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our data showed that App use for self-reporting of symptoms is feasible longitudinally, and retention rate after 3 months was still high in MiDEAR. Thus, as reported from other ePROM studies, the App use might contribute to optimized patient–doctor interactions and care [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 71%
“…Walker et al rated web-based patient assessments as useful for cost-effective monitoring between outpatient visits [ 28 ]. Further positive results and benefits from mHealth interventions have recently been summarized by Seppen et al [ 31 ]. In line with those findings our rheumatologists, who e.g., valued the App data for permitting broader views on the course of the disease, reported some positive effect on the patient-physician interaction and on therapy adherence, and recommended its further use.…”
Section: Discussionmentioning
confidence: 99%
“…HIBOOT app does not contain monitoring of patient-related outcomes as described in other apps [7]. Although studies have shown that patients favour self-monitoring health or disease activity [39][40][41] and many people with IA would agree to share their mobile app data for research purposes or regularly enter data [40], self-monitoring was suggested by only 10 patients in our quantitative study and thus was not retained.…”
Section: Discussionmentioning
confidence: 98%
“…This observation may indicate that an important proportion of French people with IA was interested in installing HIBOOT, probably close to the whole population who already used mhealth apps (i.e, 5%). The HIBOOT app life is longer than most published apps: some have shown a rapid decrease in use over a 4-week period [7], 75% people had stopped using them after 3 months [39] and only 5% of apps for rheumatic and musculoskeletal diseases were still available 2 years after their launch [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation